Thermal comfort in the productivity of students' learning at faculty of technical and vocational education - Osman, Nor Naqiuddin; Razali, Nizamuddin; Gerijih, Debie Devissr; Baharudin, Nurhayati; Nur Yunus, Faizal Amin; Ali, Khairul Fahmi (2021)
Malaysia is a tropical country with hot and humid weather throughout the year. This will cause an inconvenience to the occupants in a building. Comfort is crucial because it can affect the daily life of the occupants and cause the health of the occupants to be disturbed. This study was conducted to examine the level of student's comfort and focus on learning on the use of laboratories and tutorial rooms in FPTV buildings. The study was conducted in the form of surveys and fieldwork. Therefore, this study uses a qualitative approach through a questionnaire and uses a hygrometer tool for data collection. This study involved 119 students using labs and tutorial rooms. The reliability coefficient of Cronbach Alpha for this study is 0.88. Likert scale for comfort level and thermal sensation lot is used to measure the response of respondents. Data that has been analysed by using IBM Statistical Package for Social Science (SPSS) to frequency, mean, percentage and standard deviation. The test for the hypothesis of the study was carried out through Pearson's correlation to find the connection between thermal comforts with students' focus in the labs and tutorial rooms in the FPTV building. The study results found that thermal comfort (temperature) was not significant with the focus of the students on learning. Meanwhile, for thermal comfort (relative humidity) and thermal comfort (wind movement there is a significant relationship between the concentration of the students but at the (weak) level.